Stock Returns Indices and Changing Macroeconomic Conditions: Evidence from the Johannesburg Securities Exchange - Moodley, Fabian; Nzimande, Ntokozo; Muzindutsi, Paul-Francois (The Journal of Accounting and Management, 2022)
The growing support of the adaptive market hypothesis (AMH) suggests that the effect of macroeconomic variables on stock returns may be revisited to investigate whether it alternates with changing market conditions. This study examined the effect of macroeconomic variables on the Johannesburg Stock Exchange (JSE) indices returns under changing market conditions. Using the Markov regime-switching models, the authors examined the response of seven sector-based indices of the JSE to switching changes in macroeconomic conditions from February 1996 to December 2018. The study revealed that the influence of macroeconomic variables on the JSE indices returns is sectorspecific and varies with market conditions. A number of the variables are found to be significant in bullish conditions but not in bearish markets. The response of the JSE All-Share Index returns to changes in money supply growth rate and real effective exchange rate in bearish market conditions is positive, but negative in a bullish market condition. Similarly, inflation growth rate has a significant effect on Industrial Metal and Mining Index returns in a bear regime but showed an insignificant effect on Industrial Metal and Mining Index returns in a bull regime. The bull market condition is most dominant among JSE selected indices. The effect of macroeconomic variables on stock market returns is explained by AMH and could be better modelled by nonlinear models.